The Influence of Understanding Level, Career Perception, and Quality Motivation on PPAk Students Interest in Pursuing Chartered Accountant Certification - Kadek Adysti Ulandari; Ni Ketut Lely Aryani Merkusiwati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The interest of PPAk students in obtaining Chartered Accountant (CA) certification can enhance their competitiveness and marketability in the workforce by providing additional evidence of competence beyond academic degrees, with the quality and expertise they possess. This research aims to determine the influence of understanding levels, career perceptions, and quality motivation on the interest of PPAk students in pursuing CA certification. The study was conducted at the Faculty of Economics and Business, Udayana University, as the best state university in Bali that offers a PPAk study program with quality graduate students, with a sample of 78 PPAk students selected using non-probability sampling method with saturated sampling technique. This research proves that, based on the Theory of Planned Behavior, the level of understanding regarding students career perceptions affects the interest of PPAk students in pursuing CA certification. Maslow's theory can be used as a basis for understanding the influence of motivating factors for PPAk students regarding CA certification. The Faculty of Economics and Business at Udayana University can benefit from this research by better understanding how understanding levels, career perceptions, and quality motivation affect PPAk students' interest in pursuing CA certification. This information can then be used to assess the factors influencing PPAk students' interest. According to this study, PPAk students' interest in obtaining CA certification is positively and significantly impacted by their comprehension levels, career perceptions, and quality motivation.